Sources and Characterization of Polycyclic Aromatic and Aliphatic Hydrocarbons in Sediments Collected near Aquaculture Sites from Eastern Aegean Coast. (17th June 2021) - Pazi, Idil; Tolga Gonul, L.; Kucuksezgin, Filiz
Abstract: Marine aquaculture in Turkey is a rapidly growing sector but environmental quality of sediments in aquaculture areas has not been studied until today. The levels of petroleum hydrocarbon levels in marine sediments from three different fish farms located on the eastern coast of Aegean Sea were studied for assessing the quality status of aquaculture regions. The levels of 16 USEPA PAHs were determined with a mean concentration of 150 for Akkoy; 90 for Gulluk; 99 ng g −1 dw for Ildır sediment samples near fish farming, lower than the SQG effects range low (2460 ng g −1 dw) and threshold effect level (619 ng g −1 dw). However, the Trap sediment samples including sinking material under the edge of the cage contain significantly higher levels of aliphatics and PAHs. The results concluded that the sediments from the aquaculture sites except Traps may not cause acute biological damage. Besides, molecular ratios suggested that the PAHs were originated from pyrogenic sources for three different aquaculture areas.